Turbulent forced convection in a shell and tube heat exchanger equipped with novel design of wing baffles - Youcef, Ahmed; Saim, Rachid; Öztop, Hakan Fehmi; Ali, Mohamed (Emerald Group Publishing Ltd, 2019)
Purpose This work presents a numerical study of the dynamic and thermal behavior of a turbulent flow in a shell and tube heat exchanger equipped with a new design of baffle type wing. The implementation of this type of baffle makes it possible to lengthen the path of the fluid in the shell, to increase the heat flux exchanged on the one hand and is to capture the weakness of the shell and tube heat exchanger with segmental baffles on the other hand. Design/methodology/approach This paper aims to analyze numerically the thermo-convective behavior of water using CFD technique by solving the conservation equations of mass, momentum and energy by the finite volume method based on the SIMPLE algorithm for coupling velocity-pressure. To describe the turbulence phenomenon, the Realizable k-epsilon model is employed. The analysis is done for different mass flow rates. The parameters studied are: the fluid outlet temperature, the average heat transfer coefficient, the pressure drop, the total heat transfer rate, the effect of the geometric shape of the baffle on the thermal behavior. The purpose of this study is to propose a new design of a shell and tube heat exchanger with a high heat transfer coefficient and a lower pressure drop compared to a shell and tube heat exchanger with transverse and segmental baffles. Findings The results showed that the use of the wing baffles enhanced the heat transfer coefficient significantly and reduced the friction coefficient. Compared with segmental baffles, the wing baffles are 11.67, 18.53 and 11.5 per cent lower in the pressure drop and 1.79, 1.9 and 2.39 per cent higher in the Nusselt number for the three mass flow rates 0.5, 1 and 2 kg/s, respectively. Originality/value The originality of this work lies in proposing a three-dimensional analysis for a novel heat exchanger.
Keywords: CFD; Pressure drop; Shell and tube heat exchanger; Wing baffle